The effect of cooling rate and supplying water condition on the freezing properties of silty clay in seasonal freezing zones - Haotian Guo; Haojie Qi; Enliang Wang; Peijin Wang; Tao Song; Chao Sun (PLoS ONE, 2025)
A unidirectional freezing experiment was performed on silty clay from the Changchun area using a custom freezing apparatus to examine temperature variations, frost deformation, and moisture migration within the soil samples. The study aimed to investigate the influence of cooling rate and water supply conditions on the soil’s frost heave properties. The results indicated that under different cooling rates and water supply conditions, the internal temperature evolution of the specimens could be categorized into four distinct stages: rapid cooling, rebound and stabilization, sustained cooling, and steady state.The final temperature of specimens under open water supply conditions was 2–3°C higher than that under closed conditions. The cryostructure exhibited a reticulated pattern, and its width increased from 3–4 cm to 6–7 cm with increasing cooling rate under the same water supply condition. The cooling rate significantly affected the frost heave ratio: under closed conditions, the ratio decreased, whereas under open water supply conditions, the vertical frost heave displacement increased with higher cooling rates.Moisture migration within the specimen was notably different under the two replenishment conditions. Under open water replenishment, the water content of the soil increased near the negative-temperature top plate and decreased in the surrounding areas.